New deal law and order: how the war on crime built the modern liberal state - Gregory, Anthony (Harvard University Press, 2024)
"Anthony Gregory traces the origins of America's modern law-and-order politics to a surprising source: the New Deal, the crucible of modern liberalism. FDR's tough-on-crime agenda played a crucial role in the New Dealers' reform agenda, which greatly expanded the limits of federal power and fundamentally altered the future of the state."--